2007
DOI: 10.1186/1476-072x-6-56
|View full text |Cite
|
Sign up to set email alerts
|

The role of neighborhood level socioeconomic characteristics in Salmonella infections in Michigan (1997–2007): Assessment using geographic information system

Abstract: Background: The majority of U.S. disease surveillance systems contain incomplete information regarding socioeconomic status (SES) indicators like household or family income and educational attainment in case reports, which reduces the usefulness of surveillance data for these parameters. We investigated the association between select SES attributes at the neighborhood level and Salmonella infections in the three most populated counties in Michigan using a geographic information system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 26 publications
2
50
2
1
Order By: Relevance
“…L'écologie urbaine et les comportements des populations sont les principaux composants à étudier afin de caractériser l'exposition des populations (Ruiz, 2004 ;Thammapalo, 2005). Toutes les études menées dans ce sens ne démontrent pas systématiquement l'impact de ces facteurs environnementaux, mais elles mettent en avant la complexité des interactions entre variables, la difficulté de définition d'une échelle géographique pertinente pour l'analyse des données et la variabilité des comportements individuels à risque (Younus, 2007 ;Onwujeke, 2005 (Renault, 2007). De janvier à août 2005, 2 997 enquêtes géoréférencées ont été réalisées.…”
Section: Les Effets De Contexte à La Réunionunclassified
“…L'écologie urbaine et les comportements des populations sont les principaux composants à étudier afin de caractériser l'exposition des populations (Ruiz, 2004 ;Thammapalo, 2005). Toutes les études menées dans ce sens ne démontrent pas systématiquement l'impact de ces facteurs environnementaux, mais elles mettent en avant la complexité des interactions entre variables, la difficulté de définition d'une échelle géographique pertinente pour l'analyse des données et la variabilité des comportements individuels à risque (Younus, 2007 ;Onwujeke, 2005 (Renault, 2007). De janvier à août 2005, 2 997 enquêtes géoréférencées ont été réalisées.…”
Section: Les Effets De Contexte à La Réunionunclassified
“…Studies have ranged from analysis of geographic variation in the use of surgical procedures (17) and prevalence of drug use across school districts (9), to the examination of the relationship between ethnicity, low birth weight, and area socioeconomic status (SES) (24) and tracking movement of the AIDS epidemic (21). GIS has had only limited use in research of food safety and foodborne illness (FBI) when compared with other areas of public health research (11,14,38). Younus et al (38) used GIS technology to examine the role of neighborhood SES on rates of Salmonella infections in Michigan over a 10-year period.…”
mentioning
confidence: 99%
“…Hedberg et al, in the United States, studied the differential characteristics between restaurants in which outbreaks did and did not occur, and found that only a qualification in kitchen management that included training in food hygiene influenced the results (Hedberg et al, 2006). An ecological study by Younus et al also found that the educational level influences the appearance of cases of gastroenteritis due to Salmonella partly due to greater discretionary income which enables eating outside the home more frequently (Younus et al, 2007). A study of individuals in Denmark by Simonsen, Frisch, and Ethelberg (2008) also found an association between higher socioeconomic level and specific enteric infections such as Salmonella, Campylobacter or Yersinia.…”
Section: Discussionmentioning
confidence: 95%